Influence of Internal Control System Effectiveness and Government Accounting Standards Implementation on Financial Report Quality - Zahraini, Nieska Sekar; Fithri, Eka Jumarni; Choiruddin, Choiruddin (Jurnal Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study examines whether the effectiveness of the Internal Control System (ICS) and the implementation of Government Accounting Standards (GAS) affect the quality of financial reports in local government institutions in Palembang City. It aims to understand how these factors, both individually and jointly, improve the reliability, clarity, and responsibility of financial disclosures. Methodology/approach: The study involved 32 local government institutions in Palembang City and used a quantitative survey. Data were collected from 96 financial management employees through purposive sampling and analyzed using multiple linear regression with SPSS version 25. Results: The findings indicate that the effectiveness of ICS positively and significantly influences the quality of financial reports. The execution of GAS also has a beneficial and noteworthy impact. Additionally, both factors concurrently affect the integrity of financial reports of Palembang’s local government agencies. Conclusions: This study confirms that the standard of financial reports generated by local government bodies is reliant on the efficiency of internal controls and the appropriate application of GAS, thus promoting accountability and transparency in the financial management of local governments. Limitations: This research is limited to three variables: ICS effectiveness, GAS implementation, and financial report quality tested both partially and simultaneously in 2025. The research object includes all local government institutions in Palembang City, with respondents involved in the preparation of financial reports. Contributions: This study highlights that the financial report quality in local governments depends on effective internal controls and proper implementation of Government Accounting Standards (GAS), which strengthen accountability and transparency.